Modulation of mammalian immune response and oxidative status by dietary Saccharomyces cerevisiae - Sivinski, Sarah E. (Kansas State University, 2018)
Saccharomyces cerevisiae contains multiple components within its cell wall, including β-glucan and mannans. This yeast species, along with its cell wall components, has been shown to modulate various functions of the immune system, intestinal cells, and whole animal health. In dairy cow health, much emphasis is placed on the transition from late gestation to early lactation, a period characterized by immunosuppression, inflammation, and oxidative stress. Sixty-four Holstein cows (50 multiparous, 14 primiparous) were either fed a control diet or control diet plus 18.4 g/d of Saccharomyces cerevisiae fermentation product (SCFP) from -29 ± 5 to 42 d relative to calving. Supplementation of SCFP generally did not affect measures of oxidative status, inflammation, innate immune response, or adaptive immune response. However, SCFP-supplemented cows tended to have lesser α-tocopherol concentrations in plasma 2 wk before parturition, and mean plasma retinol concentrations were greater for SCFP-supplemented primiparous cows but lesser for SCFP-supplemented multiparous cows compared to parity-matched controls. Additionally, primiparous cows supplemented with SCFP tended to have greater serum concentrations of anti-ovalbumin immunoglobulin G after subcutaneous ovalbumin vaccinations postpartum. An in vitro cell screening system using RAW 264.7 murine macrophages and human intestinal epithelial Caco-2 cells also identified immunomodulatory effects of live S. cerevisiae and S. cerevisiae-derived β-glucan, mannan, and zymosan, a crude cell wall preparation containing both β-glucan and mannan. D-mannose was also evaluated as the monomer of mannan. RAW cells were transfected with a vector that drives expression of alkaline phosphatase upon activation of nuclear factor κ-light-chain-enhancer of activated B cells (NFκB), a major inflammatory/immune transcription factor. Messenger RNA abundance for the pro-inflammatory cytokine, IL-8, and the tight junction protein, claudin-1, was evaluated in Caco-2 cells. RAW and Caco-2 cells were each incubated with 0.01, 0.1 or 1 mg/mL of these treatments alone or pre-incubated with these treatments followed by a lipopolysaccharide (LPS) challenge. Additionally, RAW cells were challenged with LPS then incubated with treatments. In RAW cells, treatment with zymosan or β-glucan alone induced NFκB activation in a dose-dependent manner, while treatment with D-mannose, mannan, or live S. cerevisiae cells did not. Pre-treatment with zymosan or β-glucan followed by an LPS challenge increased NFκB activation, whereas pre-treatment with D-mannose and mannan decreased NFκB activation, indicating that these components may protect against LPS-induced inflammation. Post-treatment with mannan and live S. cerevisiae after an LPS challenge decreased NFκB activation, suggesting that these treatments may ameliorate LPS-induced inflammation. Treatment with live S. cerevisiae at 1 mg/mL alone or followed by LPS challenge decreased, whereas treatment post-LPS challenge increased, measures of RAW cellular metabolism. Evaluation of live cell treatments may not be accurate with this in vitro screening system. In Caco-2 cells, treatment with β-glucan at 0.01 mg/mL, mannan at 1 mg/mL, and zymosan at 0.1 and 1 mg/mL increased IL-8 mRNA abundance with treatment alone or followed by an LPS challenge. Interestingly, β-glucan-induced IL-8 mRNA abundance was greater without LPS stimulation. In contrast, claudin-1 mRNA abundance did not differ among treatments. Live S. cerevisiae cells also increased measures of Caco-2 cell viability. Overall, S. cerevisiae and its cell wall components modulated innate immunity in vitro, whereas SCFP modulated some aspects of oxidative status and adaptive immunity in transition dairy cows.
Keywords: Saccharomyces cerevisiae; Nutritional immunology; Transition dairy cattle; In vitro cell screening system; Oxidative stress; Inflammation